Assessing the performance of Random Partitioning and K-Fold Cross Validation methods of evaluation of a Face Recognition System - Babatunde, Ronke Seyi; Olabiyisi, S O; Omidiora, E O; Ganiyu, R A; Isiaka, A (European Journal of Applied Sciences, 2016)
Face recognition has been an active research area in the pattern recognition and computer vision domains due to its many potential applications in surveillance, credit cards, passport and security. However, the problem of correct method of partitioning the face data into train and test set has always been a challenge to the development of a robust face recognition system. The performance of the System was tested on locally acquired face database when the face database was randomly partitioned and when k-fold Cross Validation partition was used.  The face database was captured under the condition of significant variations of rotation, illumination and facial expression. Quantitative evaluation experimental results showed that Random Sampling technique has a higher average recognition rate (96.7%) than Cross Validation partition method (95.3%).  However, recognition time in Cross Validation is faster (0.36 secs) than that of Random Sampling (0.38 secs).